Achievement Growth Performance (AGP): Definition, Connotation, Characteristics and its Value - Liu, Liming; Noor Raihani, Zainol; Tan, Julia, Yin Yin (INTI International University, 2025)
This paper introduces Achievement Growth Performance (AGP), a novel and comprehensive concept that integrates students' motivation, continuous ability growth, and academic performance into a dynamic developmental framework. Unlike traditional performance metrics that solely concentrate on static academic achievement, AGP emphasizes a holistic growth trajectory, encompassing learning initiative, skill acquisition, personal development, and long-term educational outcomes. AGP is designed to comprehensively measure students' motivation for growth, their process of comprehensive development and enhanced abilities, and the overall quality improvement process and its ultimate outcomes. It transcends the conventional focus on a single metric of "academic achievement," highlighting that students should not only achieve specific results but also demonstrate comprehensive development. This concept is based on the integration of two established theories: achievement motivation theory, proposed by McClelland and Atkinson, and performance theory. AGP has significant potential to revolutionize performance methodologies and educational models by shifting the focus from simple "score ranking" to a comprehensive "growth trajectory". This document lays the groundwork for continuous investigation and application of this groundbreaking idea, suggesting further research could quantify AGP through metrics like a 'Growth Performance Index' and explore its adaptability in diverse cultural settings.